Two criticisms of natural theology - Gębura, Błażej (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2014)
The article aims at considering two general criticisms often formulated against the natural theology. First criticism is based on the thesis that the conclusions of the natural theology are not adequate with the religious beliefs of non-philosophers. It is widely known as opposition between God of Religion and God of Philosophers. One can find that argument in the writings of Blaise Pascal. I’m arguing for the thesis, that the natural theologian cannot fulfill the criteria given by the proponents of this argument. This is because the argument of the natural theology cannot contains the premises taken from the Revelation. If the argument of the natural theology would contain the premises taken from the Revelation, then it would be the argument of religion. But philosopher of religion (natural theologian) can’t do this, if he wants to formulate an philosophical argument. The second criticism is based on the notion of a rational person. In the light of this argument, the natural theology is successful only, if every rational person will accept the conclusion “God exist”. I’m trying to show that there is no philosophical argument that can guarantee it’s acceptance by some rational persons. The acceptance of the conclusion of the argument of the natural theology is a matter of personal decision. There is no logical argument, which can “force” rational persons (rational subjects) to accept it’s conclusion. But if this is true, the arguments for the existence of God are no worse than other philosophical arguments.